ANTIBACTERIAL EFFECTIVENESS TEST OF KECAPI LEAVES EXTRACTS (Sandoricum koetjape) AGAINST THE GROWTH OF Porphyromonas gingivalis - Novita Nanda Fitria; Beta Widya Oktiani; Aulia Azizah (FKG ULM, 2024)
Background: Chronic periodontitis is a disease of the oral cavity that is influenced by the presence of plaque bacteria caused by Porphyromonas gingivalis which can cause chronic infection of the periodontal tissue. Kecapi leaf (Sandoricum koetjape) extract contains active compounds in the form of flavonoids, saponins, alkaloids, steroids, phenolics, and triterpenoids which function as antibacterial against the growth of Porphyromonas gingivalis. Kecapi leaf extract is used as an alternative to using herbal gluconate to prevent infection caused of Porphyromonas gingivalis. Purpose: To determine the antibacterial effectiveness of kecapi leaf extract against bacterial growth of Porphyromonas gingivalis. Methods: This study used a pure experimental research (true experimental) with post-test only with control design, consists of 7 treatment groups, including: concentrated kecapi leaf extract 5%, 10%, 15%, 25%, 50%, chlorhexidine gluconate 0.2% as positive control, and distilled water as negative control. It was repeated 7 times, the antibacterial effectiveness was assessed from Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) on BHIB and NA media by dilution method. Results: MIC on kecapi leaf extract at a concentration of 5% showed the smallest result of -0.147 and the MBC value at a concentration of 50% did not show the growth of bacterial colonies. Conclusion: Kecapi leaf extract with concentrations of 5%, 10%, 15%, 25%, 50%, and positive control was effective in inhibiting and killing bacterial growth of Porphyromonas gingivalis. Keywords: Antibacterial, Kecapi leaf extract, Porphyromonas gingivalis